(untitled) (Journal of Forest and Livelihood, 2024)
This article briefly outlines individually distributed plot based forestry practices of a forest user group (FUG) in eastern Terai of Nepal. Forest users have adopted this system to enhance livelihoods impacts of forest, although there is no explicitly designed national policy and legislation to support it. Raktamala Community forest user group, which is located in the eastern Terai district of Saptari, is one that has been practicing this type of system. Most of 620 households affiliated to the group use about a half of the 350 hectares of community forests as individually-owned forest plots.